India and the knowledge economy: overview and global context - Singh, Surjit (2005)
The author argues that India has a long way to go to fully cherish the fruits of knowledge. There is great potential for increasing productivity by shifting labour to more productive modern sectors and to new knowledge based activities. This would help in poverty reduction and social welfare enhancement. There is need to strengthen existing institutions and promote new ones. Policy shift is especially required in the education sector. - Reproduced.
Keywords: Knowledge management - India; Knowledge management